PERSEPSI PESERTA DIDIK DAN PENGARUH PEMBERIAN TUGAS TERHADAP HASIL BELAJAR MATERI KEBIJAKAN EKONOMI - Nurul Mufidah, (Pendidikan Ekonomi, 2013)
The purpose of this study is to find out the effect of giving the assignment toward the learning outcomes on Economics lesson. The type of this study is descriptive with quantitative approach. This study employs the purposive sampling and use one class as the object. The data gathered trough the questionnaire and interview. Analytical technique used in this study is a simple linier regression. The data analysis and hypothesis test shows the significant effect of giving the assignment on the learning outcomes.